(3cfR GdOQQs - (3CHh HcQ YHO Gddg Hf CjHc GdOhGOGQjs
(3ChdgG (B:s
(3GdMeO ddg GdPi Ndb BOe ef ZjQ HTQ hHYO aEf Gdbhd bO JbOe ef GdYHO GdMbjQ CHh HcQ Hf YHO Gddg Hf CjHc hdeG eVi Gdbhd ai GdLRA GdChd PcQ EfbVGA eOg GdYGde hEHJOGFg hENJdGa GdYdeGA ai Pdc s
(3BNQgG (B:s
(3hbjd dEKfJi YTQg ef Chd YGe GdgLQI , hGdNdjaI jheFP YeQ Hf GdNWGH QVi Gddg Yfg hGdUMjM Cf Pdc cGf ai SfI SHY YTQg hGddg YR hLd CYde fLR hddg hGdMeO hGdefg s
(3GdfSNI HgG MhGTs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJGQjNs